Combine terms: 12a + 26b -4b – 16a.
(a) 4a + 22b,
(b) -28a + 30b,
(c) -4a + 22b,
(d) 28a + 30b.
Answers
Answered by
27
❤️_______
________❤️
✌️_______UR ANSWER_______✌️
![<u>Solutions <u>Solutions](https://tex.z-dn.net/?f=+%26lt%3Bu%26gt%3BSolutions)
12a + 26b -4b – 16a.
= 12a – 16a + 26b – 4b.
= -4a + 22b.
Answer: (C)
⤴️_____HOPE HELP YOU_____⤴️
✌️_______UR ANSWER_______✌️
12a + 26b -4b – 16a.
= 12a – 16a + 26b – 4b.
= -4a + 22b.
Answer: (C)
⤴️_____HOPE HELP YOU_____⤴️
Answered by
36
Answer-:
12a+26b-4b-16a
=> 12a-16a+26b-4b
=>-4a+ 22b
So correct option is (C)
Be brainly.....☺️
12a+26b-4b-16a
=> 12a-16a+26b-4b
=>-4a+ 22b
So correct option is (C)
Be brainly.....☺️
AJAYMAHICH:
then
Similar questions
Political Science,
8 months ago
Social Sciences,
8 months ago
Chemistry,
1 year ago
Math,
1 year ago